Temporary Frontal Paralysis Secondary to Blunt Trauma Frontal Sinus Fracture - Mark Bastianelli; Stefan Hamilton; Matthew Hearn; Safeena Kherani; Kristian I. Macdonald (Case Reports in Otolaryngology)
Frontal sinus fractures (FSF) are relatively uncommon and can be challenging for trauma surgeons to manage. Patients with FSF typically present with facial swelling, pain, and nasofrontal ecchymosis. Here we present a rare case of a patient with FSF and anterior table fracture where the main presenting symptom was bilateral frontal paralysis. We outline our management strategy and review the current literature in regard to management of FSF.